Strengthening Innovation in Nicaragua through Technology and Innovation Support Centers (CATI) - Herrera Castrillo, Cliffor Jerry (Revista Multi-Ensayos, 2025)
In Nicaragua, the Technology and Innovation Support Centers (CATI) are pillars in the promotion of research, innovation and protection of intellectual property; the first CATI was reportedly installed in 2015 at UNAN-Managua and currently there is a network of seven CATI, operating in universities nationwide (UNAN-Managua, UNAN-León and UNI). These, in collaboration with the Ministry of Development, Industry and Commerce (MIFIC), provide access to specialized databases, advice on intellectual property and support to entrepreneurs and SMEs, in line with the National Plan to Fight Poverty and Human Development and the National Strategy “Blessings and Victories.”